Keanekaragaman Vegetasi Pada Habitat Yang Terinvasi Tumbuhan Invasif Di Hutan Kota Bukit Langkisau Painan, Sumatra Barat - Dika Putri Sehati; Solfiyeni Solfiyeni (Universitas Andalas, 2023)
The presence of invasive plants in a habitat will cause significant disturbances, especially in decreasing the abundance of biodiversity. The high competitiveness of invasive species causes native species to lose in competition. Invasive species have spread in many places, one of which is in the Bukit Langkisau City Forest. However, data on the types of weeds and vegetation types in the habitats invaded by weeds in the Bukit Langkisau City Forest are not yet available. Vegetation analysis was carried out in the Bukit Langkisau Painan City Forest, West Sumatra. The study used a survey method by laying out plots by purposive sampling, which made 15 plots at each level of vegetation. The plot is 10 x 10 m for observation of tree-level vegetation, the plot is 5 x 5 m for sapling vegetation and for understorey vegetation the plot is 2 x 2 m. The results of the vegetation analysis recorded 87 species of which there were 32 invasive species. The dominant families were found such as Fabaceae family, Meliaceae for tree level, Piperaceae for sapling level and Poaceae for understorey level. The highest Importance Value Index for tree vegetation, sapling and understorey was found in the invasive species Swietenia macrophylla (IVI = 44.69%), Piper aduncum (IVI = 85.08%), and Imperata cylindrica (IVI = 33.67%). The Vegetation Diversity Index in the Bukit Langkisau City Forest is the tree level (1.90), sapling (1.26) and understorey (1.78) which are all classified as moderate. KEYWORDSPlant invasive, urban forest, composition, structure, diversity index